Associations between systemic immune-inflammatory index and visceral adipose tissue area: results of a national survey - Liao, Yayun; Zhou, Kejian; Lin, Baoquan; Deng, Shan; Weng, Baohui; Pan, Liya (Frontiers in Nutrition, 2025)
BackgroundGlobal health issues related to obesity are growing. Visceral adipose tissue (VAT) significantly contributes to complications associated with obesity. Reducing adipose tissue accumulation can improves inflammation. However, it is still unknown how the systemic immune-inflammation index (SII) and VAT area are related.MethodsWith the help of multivariate linear regression and smooth curve fitting, the relationship between SII and VAT area was explored with data from the 2013 and 2014 National Health and Nutrition Examination Survey (NHANES). Analyzing subgroups and testing for interaction were used to investigate whether the relationship was accurate across demographics.ResultsFrom 20 to 59 years of age, 3,290 individuals were observed to have a positive correlation between SII and VAT area. In accordance with the fully adjusted model, the VAT area increased by 9.34 cm2 for every unit increase in log SII [β = 9.34, 95% CI (4.02, 14.67)]. In the highest quartile of SII, the VAT area was 5.46 cm2 [β = 5.46, 95% CI (2.21, 8.71)] higher than that in the lowest quartile. Additionally, the population that was overweight or obese showed a stronger positive correlation.ConclusionSII has a positive correlation with VAT area in US adults. SII may be valuable in clinical applications to evaluate the severity of VAT area.